2022
DOI: 10.1039/d1ee03975j
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of chromia poisoned oxygen exchange kinetics in mixed conducting solid oxide fuel cell electrodes by serial infiltration of lithia

Abstract: Solid oxide fuel cells have the potential to render the conversion from fuel to electrical energy more efficienct while lowering emissions. The technology, however, suffers from performance degradation due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…78,79 A common property of all these oxides is their acidity relative to usual SOFC cathode material surfaces. 27,[80][81][82] While this fact has already been recognized previously, 27,81 no conclusive mechanistic explanation for the correlation of surface acidity and oxygen exchange kinetics has been brought forward yet. While a detailed experimental and theoretical investigation of different combinations of surface oxides and host materials is far beyond the scope of this study, we suspect that the mechanism behind the here investigated sulphate induced degradation plays a major role in this discussion.…”
Section: Effects Of Different Acidic Adsorbatesmentioning
confidence: 98%
“…78,79 A common property of all these oxides is their acidity relative to usual SOFC cathode material surfaces. 27,[80][81][82] While this fact has already been recognized previously, 27,81 no conclusive mechanistic explanation for the correlation of surface acidity and oxygen exchange kinetics has been brought forward yet. While a detailed experimental and theoretical investigation of different combinations of surface oxides and host materials is far beyond the scope of this study, we suspect that the mechanism behind the here investigated sulphate induced degradation plays a major role in this discussion.…”
Section: Effects Of Different Acidic Adsorbatesmentioning
confidence: 98%
“…This insures that the contribution of gas phase diffusion and bulk oxygen ion diffusion to the overall kinetics are negligible, as vigorously examined and confirmed in our preceding studies. [23,28] As a consequence, the overall redox kinetics are solely limited by the oxygen surface exchange reaction. The pristine specimen was first measured and then infiltrated with the Si-species at a dilute concentration of 0.02 at% with respect to PCO and re-measured.…”
Section: Poisoning and Recovery Of The Oxygen Exchange Kineticsmentioning
confidence: 99%
“…where k B is the Boltzmann constant, T the temperature in Kelvin, and c O the total concentration of lattice oxygen (5.035 10 22 cm -3 ). [33] As k el is derived from experiments that rely on the response to changes in electrical potential (impedance spectroscopy), while k chem is determined from experiments that rely on the response to changes in chemical potential (pO 2 step in conductivity relaxation), to properly compare them one must take into consideration the thermodynamic factor (w e ) [23,42] and surface area (S A ) as in the following relation: [28] k S k w k T e R c w…”
Section: Evaluation Of Electrochemical Performancementioning
confidence: 99%
“…Ji et al suggested that gas diffusion in porous CeO 2Àd does not have an effect on the surface exchange kinetics when the temperature is below 1100 1C, 24 while Seo et al found that gas diffusion can be ignored for porous Pr 0.1 Ce 0.9 O 2Àd below 600 1C. 36 The inhomogeneous surface exchange rate at different gassolid interfaces is another intractability and inevitable problem, which is mainly caused by the inhomogeneity of p O 2 and particle size for a porous material. The inhomogeneity in oxygen partial pressure, which originates from gas diffusion in pores, is determined by the porosity (e), pore radius (r, cm), and gas diffusion depth (L d , cm).…”
Section: Possible Physical Process For Orr In Porous Miec Electrodementioning
confidence: 99%
“…), Ruddlesden-Popper oxides (La 2À2x Sr 2x Ni 1Àx MnO 4+d , 45 Nd 2 NiO 4+d , 46 La 2 NiO 4+d 47), and fluorite solid solutions (PCO). 36…”
mentioning
confidence: 99%